Penguatan Kemampuan Kebahasaan Siswa Kelas X Melalui Pembelajaran Kontekstual pada Materi Teks Hikayat XE-7 MAN 2 Kota Malang - Riza, Raisha Nurul; Glorin, Grace; Salsabila, Qonita Muhimma; Abadi, Machrus (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2024)
The ability of students to comprehend hikayat texts remains a challenge due to the linguistic complexity of hikayat, which incorporates both standard Malay and archaic forms. This study aims to address the question of an effective learning model that can provide optimal solutions for the students of class XE-7 at MAN 2 Malang City. Using a qualitative approach, the research employed interviews with teachers to identify learning-related problems, classroom observations to examine the learning environment, and documentation as evidence for the learning process and outcomes. Data collection included questionnaires to evaluate students’ experiences during the learning process and their comprehension of hikayat texts. The findings revealed that contextual learning methods significantly enhanced students' ability to understand and engage with hikayat texts. The students demonstrated strong performance in answering questions related to the material and reported that contextual learning made lessons more comprehensible and engaging. These results suggest that incorporating contextual learning strategies can improve student comprehension and learning outcomes in studying hikayat texts.